2022
DOI: 10.29333/iejme/11471
|View full text |Cite
|
Sign up to set email alerts
|

The Integer Test of Primary Operations: A Practical and Validated Assessment of Middle School Students’ Calculations with Negative Numbers

Abstract: Skills and understanding of operations with negative numbers, which are typically taught in middle school, are crucial aspects of numerical competence necessary for all subsequent mathematics. To more swiftly and coherently develop the field's understanding of how to foster this critical competence, we need shared measures that allow us to compare results across studies with diverse populations and theoretical perspectives. Yet, to date no validated instrument exists to assess all four primary operations (addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For instance, student accuracy ranged from about 33% to 67% on integer subtraction items depending on item structure (Nurnberger-Haag, Kratky, & Karpinski, 2022, p.11;Periasamy & Zaman, 2009, p.366;Ryan & Williams, 2007, p.218). A Rasch analysis of the Integer Test of Primary Operations confirmed that integer subtraction overall was the most difficult operation for middle grade students (Nurnberger-Haag et al, 2022). Subtraction problem structures that result in a positive solution are the most difficult (Nurnberger-Haag et al, 2022).…”
Section: Integer Knowledge and Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, student accuracy ranged from about 33% to 67% on integer subtraction items depending on item structure (Nurnberger-Haag, Kratky, & Karpinski, 2022, p.11;Periasamy & Zaman, 2009, p.366;Ryan & Williams, 2007, p.218). A Rasch analysis of the Integer Test of Primary Operations confirmed that integer subtraction overall was the most difficult operation for middle grade students (Nurnberger-Haag et al, 2022). Subtraction problem structures that result in a positive solution are the most difficult (Nurnberger-Haag et al, 2022).…”
Section: Integer Knowledge and Learningmentioning
confidence: 99%
“…A Rasch analysis of the Integer Test of Primary Operations confirmed that integer subtraction overall was the most difficult operation for middle grade students (Nurnberger-Haag et al, 2022). Subtraction problem structures that result in a positive solution are the most difficult (Nurnberger-Haag et al, 2022). Integer subtraction is particularly difficult, because in early elementary school students' extensive experience with subtraction always decreases quantities, which makes it counter-intuitive that subtracting a negative integer increases the value (Periasamy and Zaman, 2009;Ryan & Williams, 2007).…”
Section: Integer Knowledge and Learningmentioning
confidence: 99%
See 3 more Smart Citations